Influence of Micro Silica and Portland Cement on Geopolymer Concrete Containing Recycled Asphaltic Concrete Aggregate - Athika Wongkvanklom; Patcharapol Posi; Puridet Kotaniwong; Phatsarapha Chakamnan; Piyawat Foytong; Sumrerng Rukzon; Prinya Chindaprasirt (Salehan Institute of Higher Education, 2026)
In this paper, the influence of micro silica (MS) and Portland cement (PC) on geopolymer concrete containing recycled asphaltic concrete aggregate was examined. The basic mix consisted of high-calcium fly ash (HFA), river sand, crushed limestone, recycled asphaltic concrete aggregate (RACCA), sodium silicate, and sodium hydroxide. Coarse aggregate was replaced with RACCA at 0, 20, and 40% by weight. MS and PC were used as hybrid additives to partially replace HFA. The tested MS-to-PC ratios were 0:10, 2.5:7.5, 5:5, and 10:0 by weight. Values were obtained for slump flow of 69-76 cm, 28 day compressive strength of 22.3-63.9 MPa, flexural strength of 2.20-4.70 MPa, shear bond strength of 6.45-19.90 MPa, and bond strength between geopolymer concrete and rebar of 4.95-7.30 MPa. The mix with 20% RACCA and an MS-to-PC ratio of 2.5:7.5 hybrid additive produced the best performance with values for compressive strength of 57.4 MPa, flexural strength of 4.30 MPa, slant shear bond strength of 16.69 MPa, and bond strength to rebar of 6.78 MPa. Thus, based on the results, RACCA could be used to make high-strength concrete according to the ACI 363.2R-11 standard, using MS and PC as enhancing materials.